2020
DOI: 10.1039/d0cc04955g
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemoenzymatic synthesis in advancing trehalose analogues as tools for combatting bacterial pathogens

Abstract: Trehalose, a disaccharide of glucose, is increasingly recognized as an important contributor to virulence in major bacterial pathogens, such as Mycobacterium tuberculosis, Clostridioides difficile, and Burkholderia pseudomallei. Accordingly, bacterial trehalose...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 140 publications
(286 reference statements)
0
21
0
Order By: Relevance
“…These CRs can form active sites that usually have loops. CDs of GH enzymes contain well-known trehalase signature motifs, motif 1 (PGGRFXEXY[G/Y] D[S/T] Y] and motif 2 (QWD[Y/F]PN/Y) [G/A] W[P/A] P), whereas GH65 and GH15 trehalases do not [ 48 , 49 ]. Our Antarctica isolate S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These CRs can form active sites that usually have loops. CDs of GH enzymes contain well-known trehalase signature motifs, motif 1 (PGGRFXEXY[G/Y] D[S/T] Y] and motif 2 (QWD[Y/F]PN/Y) [G/A] W[P/A] P), whereas GH65 and GH15 trehalases do not [ 48 , 49 ]. Our Antarctica isolate S .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the acquisition of an additional cluster of trehalose metabolism genes, namely a second PTS that mediates high-efficiency trehalose uptake from the environment, epidemic C. difficile strains can also grow on low trehalose. By increasing toxin levels, both modified trehalose utilization systems contributed to the growth and toxicity of these epidemic C. difficile strains [ 49 ]. There have been no previous papers on the function of the trehalose degradation pathway in virulence in Antarctic isolates till date.…”
Section: Resultsmentioning
confidence: 99%
“…The recombinant transketolase from S. elongatus was used as robust catalyst, and especially stereoselective sugar synthesis benefits from chemoenzymatic strategies. [42] Thus, five new 7dSh analogues (2-6) originated from this approach, whereby four turned out to be in vitro inhibitors of the A. thaliana DHQS in a micromolar range. Modification of the C-5 residue confirmed that the amount of pyranosyl form of the inhibitor and the presence of the hydroxyl group at C-5 with the correct stereo configuration are equal antagonists in this SAR study.…”
Section: Discussionmentioning
confidence: 99%
“…This straightforward approach enabled us to expand the novel compound family of 7dSh analogues, a potential herbicide class which demands a chemical structure‐activity relationship study with careful transport and plant assays. The recombinant transketolase from S. elongatus was used as robust catalyst, and especially stereoselective sugar synthesis benefits from chemoenzymatic strategies [42] . Thus, five new 7dSh analogues ( 2 – 6 ) originated from this approach, whereby four turned out to be in vitro inhibitors of the A. thaliana DHQS in a micromolar range.…”
Section: Discussionmentioning
confidence: 99%
“…The chemoenzymatic synthesis of other trehalose analogs has been reported previously. [73,74] We are now analyzing the genomic DNA sequence of the producing strain and trying to find the enzymes to biosynthesize 4-trehalosamine. If the producing enzymes become applicable, significant amounts of 4-trehalosamine could be produced from starch and some nitrogen sources at a low cost, similar to the current mass production of trehalose.…”
Section: Mass Producibility Of 4-trehalosaminementioning
confidence: 99%